Understanding how socio-ecological factors affect resilience and persistence among students in engineering education in South Africa - Mostert, Morney Conrad (Department of Electrical Engineering, 2025)
Resilience is paramount in the demanding sphere of tertiary studies, particularly in engineering programmes that require significant cognitive and emotional investment. Guided by Ungar's Socio-Ecological Model of Resilience, this study examines the factors contribute to or hinder resilience and academic persistence among engineering students at a South African university of technology. The study was a qualitative analysis using insights from semi-structured interviews with seven senior engineering students. Criterion sampling was employed to deliberately exclude first-year students to ensure sufficient academic experience with rigorous theoretical coursework and intensive laboratory sessions. Seven senior engineering students participated, and data were collected via semi-structured, online interviews using Microsoft Teams, each lasting between 45 to 60 minutes. Interviews were recorded, transcribed verbatim, and analysed using Deductive Thematic Analysis. The themes were mapped explicitly onto Ungar's ecological framework, ensuring rigorous alignment between theoretical concepts and empirical data. In Ungar's framework, resilience results from active interweaving of factors at four ecological levels: macrosystem, microsystem, exosystem, and mesosystem. At the microsystem level, encouragement by members of the faculty, positive relationships with peer students, and curricular requirements that are well structured offer the greatest contributory factors to student motivation. Family and community support as well as mentorship create strong pillars within the mesosystem and are supported at the campus level. At the exosystem level, institutional policies and infrastructure demonstrate how challenges regarding access to financial aid and bureaucracy, as well as problems like unstable electricity supply, at times diminish students' resilience, but in some cases may support it. At the macrosystem level, societal perceptions of engineering as both prestigious and demanding shape students' aspirations and pressures, underscoring the need for broader cultural and systemic support. These findings refine Ungar's model by highlighting engineering-specific challenges, such as lab-intensive coursework and infrastructural constraints, and underscoring how multi-tiered interventions can foster resilience in resource-limited contexts. Practical recommendations include streamlining funding and administration, implementing empathy training for academic staff, adapting curricula to local conditions, and forging collaborative ties with families and communities. By viewing resilience as a socially anchored process rather than purely an individual trait, the study calls for coordinated efforts to empower engineering students, ultimately enriching both their academic success and the broader STEM - science, technology, engineering and mathematics - landscape in South Africa